(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article provides a brief description of what fish are and how they are adapted to their environment. At the same time, the ecological and nutritional importance of fish in human life and in the food chain is expressed